Egy év - Sipos, András (Hungary, 2014)
On the 70th anniversary of the German occupation, 12 former classmates from the Toldy school remember the tragic events. Viewing history from the perspective of a child brings a particularly unique perspective: hiding under a false name, a long summer spent with other people’s grandparents in the countryside. Some were in yellow-star houses, others in the ghetto. One lost both his hands in the bombings, others witness executions. With the participation of prominent Hungarian figures: György Kézdy, Rudolf Ungváry, János Kende and József Székely.
Film was screned within the 'Yellow-star Houses' project "10 documentary films on the persecution of the Jews", 21 June 2014.
Duration: 01:18:00